Awakening to the alcohol epidemic - need of the hour - Dharav Sunil Shah (Wolters Kluwer Medknow Publications, 2017)
Globally, alcohol has become the most common risk factor for death and disability in the young age group of 15-49 years. Its use has been rapidly increasing in developing countries. It is a critical time wherein if effective preventive measures are not undertaken urgently, damage done will be difficult to reverse. However, health professionals are not responding to the alcohol epidemic in the manner that they responded to the tobacco epidemic. The article discusses two beliefs which are making us accept the use of alcohol as normal. Recent evidence indicates that it is not advisable to drink alcohol even in moderation. Furthermore, social drinking has failed to decrease alcohol-related harm in western countries. Because of its addictive nature, many people end up drinking excessively though they do not intend to. Hence, we need to shift our focus from only "reducing harmful use of alcohol" to "reducing use of alcohol" in general.